Cyanidin-3-o-Glucoside Pharmacologically Inhibits Tumorigenesis via Estrogen Receptor β in Melanoma Mice - Liu, Mei; Du, Yaqi; Li, Haiwen; Wang, Li; Ponikwicka-Tyszko, Donata; Lebiedzinska, Weronika; Pilaszewicz-Puza, Agata; Liu, Huijiao; Zhou, Lijun; Fan, Hanlu; Wang, Mingming; You, Hua; et al. (Frontiers in Oncology, 2019)
Abstract Expression patterns of estrogen receptors [ER, ERβ and G-protein associated ER (GPER)] in melanoma and skin may suggest their differential roles in carcinogenesis. Phytoestrogenic compound cyanidin-3-o-glucoside (C3G) has been shown to inhibit the growth and metastatic potential of melanoma, although the underlying molecular mechanism remains unclear. The aim of this study was to clarify the mechanism of action of C3G in melanoma in vitro and in vivo, as well as to characterize the functional expressions of ERs in melanoma. In normal skin or melanoma (n=20/each), no ERα protein was detectable, whereas expression of ERβ was high in skin but weak focal or negative in melanoma; and finally high expression of GPER in all skin vs. 50% melanoma tissues (10/20) was found. These results correspond with our analysis of the melanoma survival rates (SRs) from Human Protein Atlas and The Cancer Genome Atlas GDC (362 patients), where low ERβ expression in melanoma correlate with a poor relapse-free survival, and no correlations were observed between SRs and ER or GPER expression in melanoma. Furthermore, we demonstrated that C3G treatment arrested the cell cycle at the G2/M phase by targeting cyclin B1 (CCNB1) and promoted apoptosis via ERβ in both mouse and human melanoma cell lines, and inhibited melanoma cell growth in vivo. Our study suggested that C3G elicits an agonistic effect towards ERβ signaling enhancement, which may serve as a potential novel therapeutic and preventive approach for melanoma.